2006
DOI: 10.1016/s0022-5347(05)01027-x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Regulation of JM-27 is Associated With the Diseased Prostate

Abstract: Despite intense research efforts, the etiology of prostatic hyperplasia associated with both benign prostatic hyperplasia (BPH) and prostate cancer remains poorly understood. Our previous studies using array technology identified JM-27 as a transcript that is dramatically up-regulated in the prostates of patients with symptomatic BPH and in normal, adjacent prostatic regions of patients with prostate cancer. In the present study, using an extended sample set, we show a correlation between the messenger RNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Utilizing antibodies generated by the Johns Hopkins site, it was revealed that JM-27 is an androgen-regulated stromal-specific protein. 19 Furthermore, based upon immunohistochemical analysis both in single samples and in tissue microarrays (TMAs), it was shown that JM-27 can distinguish at the tissue level highly symptomatic individuals from those with histologic disease. At the mRNA level, JM-27 is found to be expressed around 18 fold higher in men with highly symptomatic BPH.…”
Section: Biomarkers For Defining Histological Versus Clinical Bphmentioning
confidence: 99%
“…Utilizing antibodies generated by the Johns Hopkins site, it was revealed that JM-27 is an androgen-regulated stromal-specific protein. 19 Furthermore, based upon immunohistochemical analysis both in single samples and in tissue microarrays (TMAs), it was shown that JM-27 can distinguish at the tissue level highly symptomatic individuals from those with histologic disease. At the mRNA level, JM-27 is found to be expressed around 18 fold higher in men with highly symptomatic BPH.…”
Section: Biomarkers For Defining Histological Versus Clinical Bphmentioning
confidence: 99%